MULTIDRUG-RESISTANT STAPHYLOCOCCUS AUREUS ISOLATED FROM CATTLE MILK IN INDONESIA - Rotinsulu, Dordia Anindita; Afiff, Usamah; Maghfira, Chairani Ridha (Buletin Veteriner Udayana; Vol. 15 No. 2 April 2023DO - 10.24843/bulvet.2023.v15.i02.p20, 2023)
Staphylococcus aureus ( S. aureus ) is one of the common causes of bovine mastitis worldwide. Inappropriate use of antimicrobials in cattle farms contributes to the increase of the antimicrobial resistance of S. aureus . This study aimed to investigate the antimicrobial resistance profiles of S. aureus isolated from cattle milk. Twelve S. aureus isolated from cattle milk in Bogor, Indonesia, were tested against seven antimicrobials using Kirby-Bauer disk diffusion susceptibility test. The results revealed that 58.3 % of isolates were multidrug-resistant S. aureus . The S. aureus isolates were resistant to penicillin G (66.7 %), ampicillin (66.7 %), vancomycin (58.3 %), and bacitracin (58.3 %). Most of the isolates were susceptible to ciprofloxacin (91.7 %), gentamicin (66.7 %), and chloramphenicol (66.67 %). If clinically indicated, treatment of mastitis should consider the antimicrobial susceptibility of the causative agent.